EFEK ANTIBAKTERI SALEP EKSTRAK RIMPANG LENGKUAS PUTIH (Alpinia galangal [L] Swartz) PADA KULIT PUNGGUNG KELINCI YANG DIBUAT INFEKSI Staphylococcus aureus - Tandy, Debora; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2012)
The aim of these research were to study antibacterial effect, effective concentration, and theeffect of concentration alteration of white galangal rhizome extract ointmentto heal rabbitsback skininfected with Staphylococcus aureus. Extraction was done by maceration usingethanol 96% as solvent. Observation of healing time was done by observing infectionhealingtime on rabbits back skin after anointment treatment, which based onthe disappearance oferythema and pus. The result shows that 10% of white galangal rhizome extract ointmenteffective to heal the infection of Staphylococcus aureus. It shown by its short healing timecompared with concentration 3% and 5%. One way ANOVA result shows that there was asignificant effect between concentrations 3%, 5%,and 10%. (Fcalculation 27,30>Ftable 3,48),it meant that high concentration resultingshorter healing time.Keywords: antibacterial effect. Alpinia galangal L., Staphylococcus aureus, rabbit backskin